Trade Unions on the Reefs of Modernity - Towalski, Rafał (Warsaw Forum of Economic Sociology, 2019)
The aim of this paper is to familiarise readers with internal and external risks currently faced by trade unions. The former include problems with the mobilisation of workers, unfavourable demographic structure and competition with other trade unions. The latter mainly include changes in the labour market and the growing role of multinational corporations, driven, to a large extent, by the next phase of the industrial revolution. The paper also proposes a solution to the problem. The key to getting out of this difficult situation is greater cooperation with civil society and new social movements. This requires overcoming many barriers, especially of ideological character, within the trade union movement.